Pengaruh Marketing Mix (7P) Terhadap Kepuasan Konsumen Pada RD Cafe Kota Binjai - Diah Adhairani; Siti Aisyah; Nurbaiti Nurbaiti (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to determine the effect of marketing mix on consumer satisfaction at RD Cafe, Binjai City. This research uses quantitative methods with an associative approach. Data collection was carried out using questionnaires, observation and interviews. The number of respondents used was 385 people who were consumers of RD Cafe Binjai City. The data analysis technique in this research uses SPSS 25 data analysis. The results of this research show that promotions, people and processes have a significant effect on consumer satisfaction. Meanwhile, product, price, location and physical evidence have no effect on consumer satisfaction. The 7P marketing mix simultaneously has a significant influence on consumer satisfaction.